Pendekatan Multidimensional terhadap Aspek Hukum dalam Studi Kelayakan Bisnis: Tinjauan Yuridis, Prosedur Perizinan, Pembentukan dan Legalitas Badan Usaha, serta Implikasinya terhadap Keberlanjutan dan Pertumbuhan Ekonomi di Indonesia - Dea Amanda Putri; Gilang saka Maulana; Muhammad Choir Rivaldi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the multidimensional legal aspects in business feasibility studies, focusing on the juridical review, licensing procedures, establishment, and legality of business entities, and their implications for business sustainability and economic growth in Indonesia. The legal framework plays a critical role in ensuring that businesses operate within the bounds of the law, providing protection and opportunities for growth, particularly for Micro, Small, and Medium Enterprises (MSMEs). Through qualitative methods and library research, this study analyzes various regulations, including Law No. 40/2007 on Limited Liability Companies, Law No. 25/1992 on Cooperatives, and the implementation of the Online Single Submission (OSS) system. The findings reveal that businesses that comply with legal requirements have better access to financial resources, legal protection, and market opportunities. However, the complex bureaucracy in licensing and business formation remains a significant challenge. This research provides practical recommendations for simplifying regulations and enhancing legal understanding among business owners to foster a more conducive and sustainable business environment in Indonesia.